AGE AND SEX FEATURES OF SONOGRAPHIC LIVER PARAMETERS IN MEN AND WOMEN PODILLYA - Прокопенко, С.В.; Мельник, М.П. (World of Medicine and Biology, 2014)
On the basis of research center of Vinnitsa National Medical University named after Pirogov conducted a comprehensive survey of 114 urban men aged from 22 to 35 years and 126 women aged from 21 to 35 years. The survey included ultrasonic research of the abdomen, in which were the identified boundary of confidence intervals and magnitude percentile sonographic parameters of liver in healthy men and women of Podillya general and of different age groups and studied age and sex characteristics of these parameters. In particularin men significant age differences established only for the size of the caudate lobe of the liver; women age differences identified for the size and thickness of the left caudate liver particles. Almost all liver sonographic parameters were statistically significantly higher in men than in women.
Keywords: liver; ultrasound; mature age; sex differences